Biochemistry of Barnacle Adhesion: An Updated Review - Liang, Chao; Strickland, Jack; Ye, Zonghuang; Wu, Wenjian; Hu, Biru; Rittschof, Dan (Frontiers in Marine Science, 2019)
Barnacles are notorious marine fouling organisms, whose life cycle initiates with the planktonic larva, followed by the free-swimming cyprid that voluntarily explores and searches for an appropriate site to settle and metamorphoses into a sessile adult. Within this life cycle, both the cyprid and the adult barnacle deposit multi-protein adhesives for temporary or permanent underwater adhesion. Here, we present a comprehensive review of the biochemistries behind these different adhesion events in the life cycle of a barnacle. First, we introduce the multiple adhesion events and their corresponding adhesives from two complementary aspects: the in vivo synthesis, storage, and secretion as well as the in vitro morphology and biochemistry. The amino acid compositions, sequences, and structures of adult barnacle adhesive proteins are specifically highlighted. Second, we discuss the molecular mechanisms of adult barnacle underwater attachment in detail by analyzing the possible adhesive and cohesive roles of different adhesive proteins, and based on these analyses, we propose an update to the original barnacle underwater adhesion molecular model. We believe that this review can greatly promote the general understanding of the molecular mechanisms underlying the reversible and irreversible underwater adhesion of barnacles and their larvae. Such an understanding is the basis for the prevention of barnacle fouling on target surfaces as well as designing conceptually new barnacle-inspired artificial underwater adhesives.